2013
DOI: 10.1007/s10661-013-3246-8
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency nutrient monitoring to infer seasonal patterns in catchment source availability, mobilisation and delivery

Abstract: S. (2017). High-frequency monitoring of catchment nutrient exports reveals highly variable storm event responses and dynamic source zone activation. Abstract Storm events can drive highly variable behavior in catchment nutrient and water fluxes, yet short-term event dynamics are frequently missed by low-resolution sampling regimes. In addition, nutrient source zone contributions can vary significantly within and between storm events. Our inability to identify and characterize time-dynamic source zone contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 52 publications
6
100
0
Order By: Relevance
“…Our experiences were comparable to those reported by Bende-Michl et al (2013) who operated a similar system in the Duck River, northern Tasmania, for 2 years. In both rivers, nutrient data showed a seasonal decline in concentration from spring to summer attributed to in-stream assimilation.…”
Section: Discussionsupporting
confidence: 89%
“…Our experiences were comparable to those reported by Bende-Michl et al (2013) who operated a similar system in the Duck River, northern Tasmania, for 2 years. In both rivers, nutrient data showed a seasonal decline in concentration from spring to summer attributed to in-stream assimilation.…”
Section: Discussionsupporting
confidence: 89%
“…Collection of nutrient data at frequent intervals in aquatic systems has in almost all cases revealed much higher temporal variability than was evident in less frequent discrete sample collection (Bende-Michl et al 2013;Pellerin et al 2009Pellerin et al , 2011Pellerin et al , 2014Wild-Allen and Rayner 2014). These data also revealed patterns in nutrient dynamics that occur at yearly, seasonal, diurnal, tidal, and individual-event time-scales, which are difficult if not impossible to detect using lowerresolution data (Bende-Michl et al 2013;Bowes et al 2009;Cohen et al 2012Cohen et al , 2013Pellerin et al 2009Pellerin et al , 2011Pellerin et al , 2014Wild-Allen and Rayner 2014).…”
Section: Continuous Sensing Of Nutrients Within the Delta New Developmentioning
confidence: 97%
“…We are aware of few studies that report results from in situ high-frequency ammonium analyzers, and-not surprisingly-these studies found that ammonium, nitrate, and phosphate variability are not necessarily linked (Bende-Michl et al 2013;Gilbert et al 2013). Although there are no published studies from the Delta using in situ measurements of ammonium and phosphate, data collected by the USGS on the Sacramento River at Walnut Grove demonstrates their variability and the complex relationship they share with nitrate ( Figure 11).…”
Section: Additional Nutrient Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of variance (ANOVA) and the other tests that we have chosen are not very demanding in this matter (Lloyd et al 2014) because they do not require data with very high resolution such as data produced by continual monitoring. Highly frequent measurements can be very important for proper exploration of dynamics and patterns which is well illustrated in the research of the nutrients preformed by Bende-Michl et al (2013).…”
Section: Samplingmentioning
confidence: 99%